Large-scale, white-light, transformation optics using integral imaging. (1st April 2016) - Oxburgh, Stephen; White, Chris D; Antoniou, Georgios; Orife, Ejovbokoghene; Sharpe, Tim; Courtial, Johannes
Abstract: We describe a way to realise transformation-optical devices from structures of micro-structured sheets called generalised confocal lenslet arrays. The resulting devices should work for all visible light, and they should be relatively easy and cheap to (mass-)produce on the scale of metres, but they suffer from field-of-view limitations and significant transmission loss. Furthermore, the mapping between electromagnetic space and physical space is not through stigmatic imaging, but integral imaging. As an example application of this technology, we design and simulate an architectural window that cloaks insulation material with the aim of reducing heat loss.